Ecological Footprint of South Asian Countries: A Comparative Study (Journal of Bangladesh Institute of Planners, 2016)
Ecological footprint is being widely used as an indicator of global sustainability. The purpose of this paper is to make a comparative analysis of South Asian countries’ ecological footprint. Literature review which forms the basis of this study, reveals that India grasps the largest ecological footprint of 1063.37 million gha; whereas Sri Lanka holds the smallest footprint of 24.14 million gha. Furthermore, India holds the largest footprint and Sri Lanka grabs the smallest footprint of all the components except fishing ground which is the smallest in Nepal. The footprints of grazing land in South Asian countries are relatively marginal. Specific country based analysis of footprint components and estimation of ecological deficit or overshoot are also incorporated in this paper. Bangladesh has the lowest per person biocapacity of 0.38 gha; while the highest per person biocapacity found in Nepal (0.55 gha). It is observed that ecological footprints of South Asian countries have exceeded their biocapacity extensively. Ecological overshoot is the highest in India (- 469.04 million gha) and the lowest in Sri Lanka (-15.24 million gha). A comparison has been made in this paper among population growth, change of ecological footprint and biocapacity, GDP growth rate and HDI ratings of the South Asian countries.JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 69-80